(untitled) (Scientific journal of the Fergana State University, 2026)
This article examines the significant role of objective and subjective family factors in shaping an individual’s moral qualities. These factors are associated with family issues, relationships, values, and child-rearing methods. The article emphasizes that to enhance the effectiveness of spiritual education, it is crucial and highly responsible to teach children important moral norms from an early age through practical application. These norms include values such as justice, honesty, respect, and mutual assistance. It has been scientifically substantiated and proven that youth upbringing and the role of history are identified as the most critical indicators.